2022
DOI: 10.3389/fmicb.2022.890807
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Changes of Bemisia tabaci Asia II 1 Induced by Chilli Leaf Curl Virus Trigger Infection and Circulation in Its Vector

Abstract: Bemisia tabaci (Hemiptera: Aleyrodidae) is a highly efficient vector in the spread of chilli leaf curl virus (ChiLCV, Begomovirus) which is a major constraint in the production of chilli in South Asia. Transcriptome analysis of B. tabaci post-6 h acquisition of ChiLCV showed differential expression of 80 (29 upregulated and 51 downregulated) genes. The maximum number of DEGs are categorized under the biological processes category followed by cellular components and molecular functions. KEGG analysis of DEGs sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…In our previous study, the expression of B. tabaci TLR3 and TOB1 was found highly abundant in response to ChiLCV infection ( Nekkanti et al., 2022 ). In the present study, dsRNAs were designed to knock down B. tabaci TLR3 and TOB1 .…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…In our previous study, the expression of B. tabaci TLR3 and TOB1 was found highly abundant in response to ChiLCV infection ( Nekkanti et al., 2022 ). In the present study, dsRNAs were designed to knock down B. tabaci TLR3 and TOB1 .…”
Section: Methodsmentioning
confidence: 89%
“…Silencing of B. tabaci hsp70 and fasciclin 2 ( fas2) modulates the ChiLCV transmission ( Chakraborty and Ghosh, 2022 ). In our previous study, the differentially expressed genes (DEGs) of B. tabaci in response to ChiLCV have been reported ( Nekkanti et al., 2022 ). DEGs associated with innate immunity such as Toll-like receptor 3 (TLR3) , fas2 , transducer of erbB2.1 ( TOB1 ), and GMP reductase were highly abundant.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies on begomovirus-whitefly interactions have been conducted providing valuable information on the transcriptional variations among different cryptic species of virus-infected whiteflies ( Kaur et al, 2017 ; Geng et al, 2018 ; Hasegawa et al, 2018 ; Ding et al, 2019 ; Li et al, 2020 ; Nekkanti et al, 2022 ). However, the specific information on the CLCuMuV-whitefly interactions remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, comparative transcriptomic profiling of MEAM1 whiteflies infected with a begomovirus (Tomato yellow leaf curl virus, TYLCV) and a crinivirus (Tomato chlorosis virus, ToCV) reveals a number of transcription factors, receptors, cathepsins and hemocyanin genes involved in regulation of the insect antiviral immunity along with their possible role in the virus transmission ( Hasegawa et al, 2018 ). Another study describes the transcriptomic changes of Asia II 1 whiteflies after infection with a begomovirus (Chilli leaf curl virus, ChiLCV) revealing several candidate genes associated with virus infection and its circulative movement in the insect vector ( Nekkanti et al, 2022 ). Likewise, the transcriptional changes in the guts of TYLCV-infected MEAM1 whiteflies showed that TYLCV could activate insect immune responses and several other genes associated with intracellular signaling ( Geng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using various omics platforms, including transcriptomics, the virus-associated microeffects of begomoviruses and criniviruses have been examined for B. tabaci (MEAM1 and MED) [44][45][46][47][48][49][50][51][52][53][54]. However, what remains unclear is whether micro-effects are due to the direct effect of the virus on the vector or to the indirect effects resulting from the modulation of the physiological changes in the infected host plant following virus infection.…”
Section: Introductionmentioning
confidence: 99%